Deformabilidade ao momento fletor de ligações viga-pilar monolíticas e pré-moldadas com armadura de continuidade em edifícios de concreto - Tsutake, Alexandre Gontijo (2019)
For simplified calculation, in the design of reticulated concrete structures, it is still common to consider the monolithic beam-to-column connections as perfectly rigid and for precast beam-to-column connections the bond is usually chosen as pinned. With the advancement of technology and with the ease and precision that structural design programs have been offering, the use of analytical models that represent the behavior of the structure as accurately as possible has become a necessity for designers. The consideration of the rotation deformability by bending moment can be done by analytical models. However, to be able to rely on the results presented by any analytical model, it is necessary its validation with experimental result. This work aims to apply analytical models for the consideration of flexural deformability in monolithic and precast concrete beam-to-column connections. A literature review on the subject with some analytical models and some experimental studies is presented. Comparisons are made between a recently proposed analytical model for monolithic beam-to-column connections and experimental results available in the specialized literature. An extension to the studied model is proposed in this paper so that it can be used in internal columns. The new analytical model is verified with experimental results of precast connections. With the aid of the ANSYS software, non-linear numerical simulations were performed applying the analytical models cited, obtaining also results of force-displacement kind. The results indicate a good performance of the models covered, as well as the methodology used.